Between Norm and Practice: Dynamics of Muhammadiyah Political Communications - Muhammad Nurul Yamin (Profetik: Jurnal Komunikasi, 2024)
This study aims to describe the dynamics of Muhammadiyah political communication. The research is based on the background that Muhammadiyah is a civil society organization engaged in the socio-religious field in Indonesia and is non-political, but has political power. Muhammadiyah's political communication is studied within the framework of the theory of "social practices" developed by Anthony Giddens, and the theory of Social Reality Construction Analysis by Berger & Luckmann. The research method was carried out qualitatively with a constructive approach. The research data was obtained through official organizational documents and in-depth interviews. The results of the study show that the normativity of Muhammadiyah political communication is rooted in Muhammadiyah ideology which originates from the Al-Qur'an and as-Sunnah, and is transformed into religious understanding, social praxis, and its political communication strategy. Muhammadiyah's political communication strategy is mapped out in three forms of strategy, namely the political communication strategy of faith and good deeds, the strategy of political communication of power structure, and the strategy of national cultural political communication. The three Muhammadiyah political communication strategies work collaboratively so they are referred to as the Collaborative Political Communication Model.